KONTEKS LIVING QURAN ala UMAR BIN KHATAB: (Implementasi Konsep Hermeneutis Dalam Penentuan Kebijakan) - FINA INDATURROHMAH Fina Indaturrohmah (IAIN Madura, 2022)
Umar as a caliph as well as a friend of the Apostle has a special position in the history trajectory. His assertive and rigorous personal attitudes lead him became the Khulafa ar Rashidun who is highly respected by Muslims. However, his personal attitudes sparked uproar and even fierce opposition among Muslims at that time, especially when he served as caliph who - it was assumed - often ignored and disobeyed the text of the Quran and the Sunnah of the Prophet Muhammad SAW. This paper used a qualitative approach and specified on literature review method, by collecting data and information from various relevant literature including both text books and internet sources. The results of this study confirmed that Umar's understanding of the text is a product of contemporary Muslim thought. In addition, Umar bin Khattab's hermeneutics can be learned from his understanding of text exposition, implementation based on the text understanding, and his progressive ijtihad in producing benefit-based law.